2020
DOI: 10.15252/embj.2019104063
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell diversity associated with immune evasion in human triple‐negative breast cancer

Abstract: The tumour stroma regulates nearly all stages of carcinogenesis. Stromal heterogeneity in human triple-negative breast cancers (TNBCs) remains poorly understood, limiting the development of stromal-targeted therapies. Single-cell RNA sequencing of five TNBCs revealed two cancer-associated fibroblast (CAF) and two perivascular-like (PVL) subpopulations. CAFs clustered into two states: the first with features of myofibroblasts and the second characterised by high expression of growth factors and immunomodulatory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
382
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(416 citation statements)
references
References 90 publications
(173 reference statements)
33
382
1
Order By: Relevance
“…Whether the breast cancer repertoire of CAFs is a caricature and maybe even a reminiscence of the normal stromal cell heterogeneity remains an open question. Interestingly, however, recent single-cell RNA sequencing of breast carcinomas has resolved stromal cell diversity to include both myofibroblastic and inflammatory CAFs and not least perivascular cells [60,61]. While this concurs with our early studies, which suggested diverse cellular origins of CAFs, including resident fibroblasts and perivascular cells [62,63], our present findings suggest that lineage heterogeneity within the resident fibroblast compartment adds to the complexity.…”
Section: Discussionsupporting
confidence: 91%
“…Whether the breast cancer repertoire of CAFs is a caricature and maybe even a reminiscence of the normal stromal cell heterogeneity remains an open question. Interestingly, however, recent single-cell RNA sequencing of breast carcinomas has resolved stromal cell diversity to include both myofibroblastic and inflammatory CAFs and not least perivascular cells [60,61]. While this concurs with our early studies, which suggested diverse cellular origins of CAFs, including resident fibroblasts and perivascular cells [62,63], our present findings suggest that lineage heterogeneity within the resident fibroblast compartment adds to the complexity.…”
Section: Discussionsupporting
confidence: 91%
“…High stroma has been associated with poor prognosis in several studies [ 10 , 11 , 12 ] with favourable outcome in one study [ 13 ]. Single cell transcriptomic studies have identified the diverse phenotype of cells present in the TME, which include immune cells, cancer associated fibroblasts (CAFs), endothelial cells and pericytes [ 6 , 14 ]. There is increasing evidence to suggest that CAFs may provide a specialised niche for cancer stem cells and influence responsiveness to chemotherapy in TNBC [ 5 , 15 , 16 ] and endocrine therapy in ER+ disease [ 17 , 18 ], supported by more recent single cell sequencing studies identifying specific subtypes of CAFs in mouse and human breast tumours [ 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Single cell transcriptomic studies have identified the diverse phenotype of cells present in the TME, which include immune cells, cancer associated fibroblasts (CAFs), endothelial cells and pericytes [ 6 , 14 ]. There is increasing evidence to suggest that CAFs may provide a specialised niche for cancer stem cells and influence responsiveness to chemotherapy in TNBC [ 5 , 15 , 16 ] and endocrine therapy in ER+ disease [ 17 , 18 ], supported by more recent single cell sequencing studies identifying specific subtypes of CAFs in mouse and human breast tumours [ 14 , 19 ]. Therefore, further data to support the rationale for including TSR as a prognostic variable in breast cancer, with clinical significance, especially for TNBC which has no other existing biomarkers, would be of value in patient risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a brain tumor construct should be based on patient-derived tumor cells of interest mixed with surrounding healthy brain cells including neurons, glial cells, astrocytes, and microvascular endothelial cells [ 80 , 81 ]. However, a breast cancer construct should be designed in such a way that patient-derived breast cancer cells are surrounded by mammary epithelial cells, adipocytes, fibroblasts, and endothelial cells [ 82 , 83 ]. This approach facilitates recapitulation of the tumor type as well as the target tissue.…”
Section: An Overview Of 3d Bioprintingmentioning
confidence: 99%